Vaccination Coverage at Birth in Brazil: Spatial and Temporal Trends in the Impact of COVID-19 on Uptake of BCG and Hepatitis B Vaccines - Yan Mathias Alves; Thaís Zamboni Berra; Reginaldo Bazon Vaz Tavares; Nathalia Zini; Quézia Rosa Ferreira; Licia Kellen de Almeida Andrade; Ariela Fehr Tártaro; Maria Eduarda Pagano Pelodan; Beatriz Fornaziero Vigato; Beatriz Kuroda Silveira; Ana Luiza Brasileiro Nato Marques Assumpção; Marcela Antunes Paschoal Popolin; et al. (Vaccines)
Introduction: Vaccines are a significant public health achievement, which are crucial for child survival and disease control globally. In Brazil, the National Immunization Program (PNI) manages vaccination schedules, including essential vaccines like BCG and Hepatitis B, administered at birth. Despite achieving over 95% coverage for years, vaccination rates have declined since 2016, a trend exacerbated by the COVID-19 pandemic. This study aims to analyze spatial and temporal trends in BCG and Hepatitis B vaccination coverage at birth, identify areas with spatial variation in these trends, classify the identified trends, and investigate the pandemic’s impact on vaccination adherence. Methods: This is an ecological study with real-world data from Brazil, focusing on vaccination coverage from 2014 to 2023. Utilizing the Spatial Variation in Temporal Trends (SVTT) technique, the study identifies municipalities’ vaccination trends. It also employs time series analysis and Interrupted Time Series methods to evaluate the pandemic’s impact on vaccination rates, using data from the PNI and the Information System on Live Births (SINASC). Results: Between January 2014 and December 2023, Brazil administered 25,902,207 doses of the BCG vaccine to children at birth, with 3911 municipalities (70.24%) showing declining trends, particularly in Florianópolis. Similarly, 22,962,434 doses of the Hepatitis B vaccine were administered, with 3284 municipalities also experiencing declines. Conclusions: It is crucial that public health policies be reevaluated to address regional disparities in vaccination coverage, particularly in more vulnerable areas. Focused interventions, such as awareness campaigns, improved access to vaccination services, and strengthened monitoring, are fundamental to reversing this trend.